2022
DOI: 10.1002/chem.202103949
|View full text |Cite
|
Sign up to set email alerts
|

Ene‐Reductase: A Multifaceted Biocatalyst in Organic Synthesis

Abstract: Biocatalysis integrate microbiologists, enzymologists, and organic chemists to access the repertoire of pharmaceutical and agrochemicals with high chemoselectivity, regioselectivity, and enantioselectivity. The saturation of carbon-carbon double bonds by biocatalysts challenges the conventional chemical methodology as it bypasses the use of precious metals (in combination with chiral ligands and molecular hydrogen) or organocatalysts. In this line, Enereductases (ERs) from the Old Yellow Enzymes (OYEs) family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 130 publications
(250 reference statements)
0
33
0
Order By: Relevance
“…It has been reported that the biohydrogenation of diene compounds is catalyzed by a collection of enzyme families known as ene-reductases, such as the FMN-containing old yellow enzyme (OYE), medium-chain dehydrogenases/reductases (MDRs), and short-chain dehydrogenases/reductases (SDRs) . A variety of ene-reductases have been identified from previously untapped sources. , Such efforts have improved not only our understanding of the ecological functions and evolution of ene-reductases but also the applications of these enzymes in chemical synthesis . For instance, flavone reductase, an ene-reductase catalyzing the hydrogenation of the C2C3 bond of flavones/flavonols in the gut bacterium Flavonifractor plautii ATCC 49531, plays essential roles in gut microbial consumption and transformation of xenobiotic flavonoids .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the biohydrogenation of diene compounds is catalyzed by a collection of enzyme families known as ene-reductases, such as the FMN-containing old yellow enzyme (OYE), medium-chain dehydrogenases/reductases (MDRs), and short-chain dehydrogenases/reductases (SDRs) . A variety of ene-reductases have been identified from previously untapped sources. , Such efforts have improved not only our understanding of the ecological functions and evolution of ene-reductases but also the applications of these enzymes in chemical synthesis . For instance, flavone reductase, an ene-reductase catalyzing the hydrogenation of the C2C3 bond of flavones/flavonols in the gut bacterium Flavonifractor plautii ATCC 49531, plays essential roles in gut microbial consumption and transformation of xenobiotic flavonoids .…”
Section: Discussionmentioning
confidence: 99%
“…Biocatalytic hydrogenation of BD to 1-butene by ene-reductases may be one of the promising technologies owing to the exquisite stereoselectivity, green chemistry, and sustainability . Nonetheless, applications of biocatalysis capable of hydrogenation of BD to 1-butene for industry may also be challenging (e.g., vulnerability under harsh conditions and industrial scale); thus, a mechanistic understanding of the process (e.g., cofactor dependence and enzyme structure) will be conducive to enhancing biocatalytic performance by protein engineering for future preparative and industrial applications. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of aromatic aldehydes is a prototypical approach to preparing aromatic alcohols. Many synthetic and catalytic practices have been probed for this fundamental transformation: transition-metal-catalyzed hydrogenation, catalytic hydrogenation via H 2 , biocatalytic reductions, and conventional stoichiometric reagents (metal hydrides) dominate industrial- and laboratory-scale conversions. These practices suffer from poor selectivity and severe ecological concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Ene-reductases, also termed Old Yellow Enzymes (OYEs) based on their discovery as a yellow ferment in 1932 (Haas, 1938;Warburg & Christian, 1932), catalyze the NAD(P)H-dependent asymmetric reduction of activated C=C bonds (Karrer et al, 2021;Kumar Roy et al, 2022) (Figure 1a). The flavin-containing enzymes have been intensely analyzed with respect to their biochemical, biophysical, and structural properties, and their reaction mechanism is well understood (Peši c et al, 2017;Shi et al, 2020;Theorell & Åkeson, 1956;Tischler et al, 2020;Williams & Bruce, 2002).…”
Section: Introductionmentioning
confidence: 99%